Contribution of National Rural Employment Guarantee Program on Rejuvenation and Restoration of Community Forests in India - Angom, Juliet; Viswanathan, P. K. (Frontiers in Forests and Global Change, 2022)
Sustainable development is one of the ubiquitous paradigms of this century. Poverty, biodiversity loss and climate change are some of the obstacles to achieving sustainable development. To mitigate these encumbrances, countries have painstakingly adopted various policies and interventions. Public work programs, one of the initiatives targeting the construction of strong social safety nets through redistribution of wealth and generation of meaningful employment are increasingly being launched in developing countries. This paper is an attempt to examine the effects of phased implementation of Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) on the rejuvenation and restoration of community forests in India. Searches performed in multidisciplinary electronic databases (Web of Science, Scopus, Science Direct, PubMed, Emerald Insight, Google Scholar, Taylor and Francis Online, Wiley Online Library and Springer Link) indicated that MGREGS is one of the largest labor guarantee schemes ever recorded in India and globally, and has holistically contributed to reforestation and afforestation through its land development themes to reduce vulnerability of rural communities to recurrent droughts, floods and improve soil moisture and fertility. It is evident that MGNREGS in synergy with the government forest development programmes have the potential to promote social afforestation, reforestation and biodiversity conservation as witnessed in the Sundarbans. These have the potential to empower local people through creation of income generating activities and provision of local forest goods and services. However, the creation of forests as rural assets necessitates that emphasis should be laid on their maintenance so as to ensure that they are given their due importance for sustainable and long-term benefit of the poor rural households. This study highlights the need to perform a comprehensive assessment of forest assets that has been established through MNREGS across states in India.